The potential for cooperation between wine and tourism businesses in the provision of tourism experiences : the case of the Douro valley of Portugal - Correia, Alexandra I. (2022)
The provision of tourism experiences depends on cooperative relationships of businesses operating not only in the same, but also in complementary industries, as it is the case of wine production industry. This paper then focuses on the occurrence, or not, of inter-sectoral and/or diagonal cooperation between businesses operating in wine and tourism industries. The aim is to understand and discuss the current situation of cooperation in the region and its (potential) adoption to the provision of tourism experiences. Data here presented was collected through interviewbased face-to-face questionnaire applied to businesses' decision makers, owners/managers. Results indicate cooperation is already being adopted by many of the owners/ managers of wine and tourism businesses in the region and that although visitor experiences were not clearly indicated by respondents as one of the reasons to cooperate, offering complementary and diversified products/services and activities is one of the main reasons for businesses, particularly for tourism businesses, to cooperate with wine businesses. It was acknowledged by respondents an increasing demand for wine-related activities (as participating in harvests and wine tasting) and the need to offer adequate products/services to meet wine-related demand expectations of tourists when vising the region. The results of this paper indicate that respondents, particularly tourism businesses, recognise that this offer is the result of cooperative relationships with wine businesses. Therefore, one can say that there is a great potential for cooperation between wine and tourism in the provision of tourism experiences in this region.